Shockwaves of Political Leadership: The Impact of Trump’s Second Presidency on Global Oil Prices - Sharaf, Mesbah Fathy; Shahen , Abdelhalem Mahmoud; Mansour, El-Hussien Ibrahim; Abdelsamiea, Abdelsamiea Tahsin (International Journal of Energy Economics and Policy, 2025)
This study explores how Donald Trump’s 2024 re-election affected Brent crude oil prices using an Interrupted Time Series (ITS) model. Given the importance of U.S. political shifts on global markets, the study tests for a structural break in oil prices following the election. Using daily data from January 2022 to March 2025, it controls for key macro-financial factors: the Economic Policy Uncertainty (EPU) Index, Dow Jones Industrial Average (DJIA), and the 10-year U.S. Treasury Yield. Findings show a significant 5.25% drop in Brent oil prices immediately after Trump’s re-election, indicating initial market uncertainty. However, the trend reversed in the days after, suggesting that investor sentiment adjusted over time. A placebo test found no such effect before the election, strengthening causal claims. Additionally, a Distributed Lag ITS model revealed the decline unfolded gradually. These results echo past research linking political uncertainty to oil price volatility, highlighting the short-term sensitivity of oil markets to leadership shocks. Still, the later price recovery points to longer-term resilience. This research adds to the literature on political impacts on commodity markets, offering useful insights for investors, energy economists, and policymakers navigating politically driven market risks.